2013
DOI: 10.1007/s10964-012-9895-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms Linking Exposure to Community Violence and Academic Functioning in African American Adolescents

Abstract: African American adolescents are exposed disproportionately to community violence, increasing their risk for emotional and behavioral symptoms that can detract from learning and undermine academic outcomes. The present study examined whether aggressive behavior and depressive and anxious symptoms mediated the association between exposure to community violence and academic functioning, and if the indirect effects of community violence on academic functioning differed for boys and girls, in a community sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 97 publications
(127 reference statements)
2
45
0
3
Order By: Relevance
“…The results from our study are in line with a sizable literature showing associations between violence exposure and internalizing and externalizing behaviors (Fowler & Braciszewski, 2009) and are consistent with recent work showing that aggressive behaviors but not anxious and depressive symptoms mediate the association between community violence exposure and academic achievement (Busby, Lambert, & Ialongo, 2013). The results of the current study also fit with the literature on developmental cascades which focuses on how functioning in different developmental domains is linked (Sameroff, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The results from our study are in line with a sizable literature showing associations between violence exposure and internalizing and externalizing behaviors (Fowler & Braciszewski, 2009) and are consistent with recent work showing that aggressive behaviors but not anxious and depressive symptoms mediate the association between community violence exposure and academic achievement (Busby, Lambert, & Ialongo, 2013). The results of the current study also fit with the literature on developmental cascades which focuses on how functioning in different developmental domains is linked (Sameroff, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Frequency of victimization had the most significant impact on development of mental health disorders, especially attention problems and poor academic achievement . Exposure to community violence inversely affected school engagement and performance when mental health disorders were included . Youth exposed to chronic trauma had a higher risk for dropout as mediated by mental health disorders .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous research, Woodbridge et al (2015) found that African American middle school students were more likely than Caucasian students to report exposure to trauma. When these negative personal experiences are compounded by experiences in unresponsive educational environments, African American students are disproportionately at risk for poor outcomes (Busby, Lambert, & Ialongo, 2013).…”
Section: Responding To Trauma and Resisting Retraumatizationmentioning
confidence: 99%